Reliability and benefits of clinical examination for determining the affected level in cervical compressive myelopathic patient: a prospective study of 44 cases (Journal of Chittagong Medical College Teachers' Association, 2009)
Key words: neurological examination; compressive myelopathy; MRI; myelomere; myelomelaciadoi: 10.3329/jcmcta.v19i2.3864Journal of Chittagong Medical College Teachers' Association 2008: 19(2):12-15